Analisis Pengaruh Struktur Modal, Likuiditas dan Earning terhadap Survival Profitabilitas pada Perbankan Nasional Indonesia periode 2017-2020 - Ajeng Widyaningrum Putri; Priscilla Uning; Retnoning Ambarwati (JURNAL WIRANOMIKA, 2024)
This research analyzes the Effect of Capital Structure, Liquidity and Earning to Survival Profitability Indonesian National Banking Period 2017-2020. The purpose of this research is to analyze the influence of Capital Structure, Liquidity, and Earning to Survival Profitability Indonesian National Banking. The formulation of the problem in this study is which factors influence between capital structure, liquidity and Earning to Survival Profitability in Indonesian National Banking?. Sampling using purposive sampling method as many as 25 National Banking. The method used in this study uses classical assumption analysis, multiple linear regression analysis, t test, f test, and analysis of the coefficient of determination. The results of this study state that partially Capital Structure has no significant effect on Survival Profitability Indonesian National Banking, Liquidity partially has a significant effect on Survival Profitability Indonesian National Banking, Earning partially significant effect on Survival Profitability Indonesian National Banking.Keywords : Capital Structure, Liquidity, Earnings, and Survival Profitability.